The Implementation of Islamic Religious Education in Building Akhlak al-Karimah at Elementary School - Al-Bukhori, Afif; Daulai, Afrahul Fadhila; Haidir, Haidir (Jurnal Basicedu, 2022)
This study aims to describe the implementation of Islamic religious education in building the character of al-Karimah students at SD IT An-Naas Binjai. This study uses a qualitative approach with a descriptive study method, as an effort to describe social reality in a complex and concrete manner. Collecting data using observation techniques, interviews, and documentation studies, as well as checking it with relevant scientific articles. Data analysis was carried out interactively, through the pre-observation stage (preliminary study), implementation stage, data analysis stage, conclusion drawing stage, to reporting research results. The results of this study conclude that (1) PAI learning planning as an effort to develop the quality of student character formation is carried out at the beginning of a new school year, in the form of meeting activities (deliberations), as well as concrete results in the form of preparation of teaching materials and lesson plans; (2) PAI learning is carried out in the classroom (based on the teaching materials and lesson plans that have been prepared) and outside the classroom (covering daily programs, monthly programs and school annual programs); (3) the way teachers evaluate learning refers to the results of student report cards, changes in student attitudes and behavior, and coordination with parents regarding student learning development; and (4) factors that influence PAI learning include school readiness, sympathetic attitude (teachers care), and parental coordination with the school.